Tarine Ch'usŏk maji - Sŏn, Cha-ŭn (Uri nal kŭrimch'aek, 2014)
"Families of Dal gather together at grandmother's house to celebrate Chuseog (Korean traditional Thanksgiving). They prepare traditional foods, make Songpyeon, play various traditional games and have a wonderful time during the village festival. Through a day of Chuseog for Dal's family, the author illustrates the rich Korean culture, tradtion, customs, and shares the wisdom of life of the ancestors that is absorbed in tradition."--bookswindow.com